PENGARUH AKTIVITAS UPACARA KEAGAMAAN UMAT HINDU TERHADAP PEREKONOMIAN PEDAGANG DI PASAR BADUNG - Aprilia, Ni Ketut; Andayani, Ni Made; Ayustini, Ni Luh (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2019)
Bali is the name of one of the provinces in Indonesia. Bali is located between Java and Lombok. The capital is Denpasar, which is located in the southern part of the island. In the world, Bali is famous as a tourism destination with a unique variety of arts and culture, especially for Japanese and Australian tourists. Bali is also known as the Island of the Gods and Pulau Seribu Island. Bali which is famous for its art and culture has various places and tourism potentials that pamper every tourist visiting Bali. The majority of the population of Bali are Hindus. Many Balinese who are Hindus have activities related to their religious ceremonies based on their celebrations or so-called "rahinan". Rahinan or holy day is a day that is commemorated or privileged, because it is based on the belief that that day has meaning and function that is very very important for the life of a person (people), both because of its influence and because of the values ??contained therein so it is felt necessary to remember, sanctified, and celebrated. Commemorating the celebration of the holy day can be routine and also identical, depending on the values ??contained therein. The holiday should be celebrated on an ongoing basis with the intention to always inflame the sanctity and sacred meaning of the religion (Kompyang, 2015).